Extrusion-shear of AZ31 alloy billets with low temperature and high speed by using three-dimensional finite element modeling and experiments - Hongjun,Hu (2014)
A new kind of compound extrusion technology including direct extrusion and shears for AZ31 magnesium billets can cause plastic large deformations and high strain rates. A series of compressive tests have been done to obtain the stress-strain curves of AZ31 magnesium alloy. Three-dimensional (3D) thermo-mechanical coupled finite element modeling of forming magnesium alloy AZ31billets into small rods at certain high ram speed and low temperature by extrusion-shears have been carried out. The simulation model has been established and meshed based on symmetrical characteristic. Computed parameters including material characteristics for workpiece and die and process conditions consisting of initial billet temperature, extrusion ratio, channel angle and ram speed have been list. The evolution of temperature during extrusion-shear process, there are hardly any temperature gradients within the workpiece, but temperature in severe plastic deformation zone increase rapidly. Strain evolutions for inner billet are larger than those of border positions. The flow velocity distribution is uniform basically which avoid the extrusion cracks to a certain degree. Experiments show that the rods with good surface smoothness can be obtained by low temperature and high speed extrusion-shear, and the alloy grains are effectively refined by dynamic recrystallization (DRX).